Responsivitas Pelayanan Publik Dp3ap2kb Dalam Penanganan Kekerasan terhadap Anak di Kota Lhokseumawe - Mailis, Mailis; Muhammad Fazil; Dahlan A. Rahman; Nirzalin Nirzalin; Maryam Maryam (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study aims to analyze the responsiveness of public services provided by DP3AP2KB of Lhokseumawe City in handling cases of violence against women and children. This research employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation involving informants related to women and child protection services. The results indicate that the responsiveness of DP3AP2KB services has been implemented relatively well, as demonstrated by the officers' prompt response in receiving reports, providing information, assisting victims, and coordinating with relevant institutions. However, several obstacles remain in the implementation of services, including limited human resources, budget constraints, and inadequate supporting facilities. Improving service responsiveness requires strengthening institutional capacity, enhancing cross-sectoral coordination, and developing services oriented toward the needs of victims. In addition, continuous public education regarding reporting mechanisms and legal protection is necessary to encourage community participation and increase early detection of violence cases. Regular training for service personnel and stronger collaboration with health facilities, law enforcement agencies, educational institutions, and community organizations are expected to improve service quality, accelerate case resolution, ensure victim recovery, and strengthen sustainable protection efforts.